The Implementation of the Think Talk Write (TTW) Cooperative Learning Model to Improve Learning Motivation in Indonesian Language Content Among Fifth-Grade Elementary School Students - Nurfatkhirah Bahar; Lukman; Nur Ilmi (PT. Lontara Digitech Indonesia, 2026)
This study is an effort to improve students’ learning motivation, which was motivated by the low learning motivation of fifth-grade students at UPTD SD Negeri 12 Parepare in Indonesian language learning, particularly in writing pantun. Therefore, the author implemented the Think Talk Write (TTW) learning model to improve students’ learning motivation. This study used a classroom action research design consisting of three cycles. Each cycle included the stages of planning, implementation, observation, and reflection. The research subjects were 20 fifth-grade students of UPTD SD Negeri 12 Parepare, consisting of 13 male students and 7 female students, as well as one teacher. The research data were obtained through observation, documentation, and questionnaires. The data analysis technique was carried out through data condensation, data display, and conclusion drawing. Based on the results of data analysis, the data showed an increase in students’ learning motivation in each cycle. Based on the data obtained during the implementation of Cycles I, II, and III, the results of the study in Cycle I showed that teacher and student activities in the learning process were in the fair category (C), while students’ learning motivation was also classified as fair (C). In Cycle II, teacher activity increased to the good category (B), while student activity remained in the fair category (C), and students’ learning motivation was still classified as fair (C). In Cycle III, both teacher and student activities reached the good category (B), and students’ learning motivation increased to the very good qualification (SB). Therefore, it can be concluded that the classroom action research implementing the Think Talk Write (TTW) Cooperative Learning Model to improve the learning motivation of fifth-grade students at UPTD SD Negeri 12 Parepare in writing pantun was successful in accordance with the predetermined success indicators.